2002
DOI: 10.1073/pnas.032655399
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar cortical inhibition and classical eyeblink conditioning

Abstract: The cerebellum is considered a brain structure in which memories for learned motor responses (e.g., conditioned eyeblink responses) are stored. Within the cerebellum, however, the relative importance of the cortex and the deep nuclei in motor learning͞memory is not entirely clear. In this study, we show that the cerebellar cortex exerts both basal and stimulus-activated inhibition to the deep nuclei. Sequential application of a ␥-aminobutyric acid type A receptor (GABAAR) agonist and a noncompetitive GABAAR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
110
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 63 publications
13
110
5
Order By: Relevance
“…Specifically, non-human experiments have determined that activation of the CR is principally controlled by the cerebellar deep nuclei, specifically the interpositus nucleus (McCormick and Thompson, 1984a;Woodruff-Pak et al, 1985;Steinmetz et al, 1991;Sears and Steinmetz, 1991). Inhibitory projections from Purkinje cortical neurons modulate the activity of the interpositus, effectively manipulating the timing of the CR (Mamounas et al, 1987;Bao et al, 2002). Evidence suggests that one locus of CR timing modification is the anterior regions of cerebellar cortex (Green and Steinmetz, 2005), an area wherein lesions disrupt CR onset and peak latencies (McCormick and Thompson, 1984b;Logan, 1991;Perrett et al, 1993;Garcia et al, 1999) and, perhaps, CR acquisition (Lavond and Steinmetz, 1989;Garcia et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, non-human experiments have determined that activation of the CR is principally controlled by the cerebellar deep nuclei, specifically the interpositus nucleus (McCormick and Thompson, 1984a;Woodruff-Pak et al, 1985;Steinmetz et al, 1991;Sears and Steinmetz, 1991). Inhibitory projections from Purkinje cortical neurons modulate the activity of the interpositus, effectively manipulating the timing of the CR (Mamounas et al, 1987;Bao et al, 2002). Evidence suggests that one locus of CR timing modification is the anterior regions of cerebellar cortex (Green and Steinmetz, 2005), an area wherein lesions disrupt CR onset and peak latencies (McCormick and Thompson, 1984b;Logan, 1991;Perrett et al, 1993;Garcia et al, 1999) and, perhaps, CR acquisition (Lavond and Steinmetz, 1989;Garcia et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Early results in rabbits ranged from complete abolition of the learned responses pointing to the cerebellar cortex as the key site (Yeo, 1991) to nominal effects that suggested a more fundamental role for the AIN (McCormick and Thompson, 1984). Numerous subsequent studies measuring closure of the external eyelid or nictitating membrane have reported responses with relatively fixed and short latencies to onset (ϳ80 -150 ms) after direct lesions (McCormick and Thompson, 1984;Perrett et al, 1993;Perrett and Mauk, 1995;Garcia et al, 1999;Medina et al, 2000) or infusing GABA A antagonists into the AIN (Garcia and Mauk, 1998;Medina et al, 2001;Ohyama and Mauk, 2001;Bao et al, 2002;Ohyama et al, 2003;Aksenov et al, 2004). We previously hypothesized that these short-latency responses (SLRs) (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that picrotoxin produces a transient dose-dependent suppression of conditioned excitation (Bao, Chen, Kim, & Thompson, 2002;Mamounas, Thompson, & Madden, 1987). The nearly complete but transient suppression of CRs at higher doses of picrotoxin temporarily precludes the analysis of its effects on discriminative responding.…”
Section: Introductionmentioning
confidence: 99%